Desenvolvimento e análise de células solares base N com emissor seletivo formado por radiação laser - Salvador, Vítor Freire e (2019)
With the solar cell industry having n+pp+ cell structures as its production base and, having in mind that solar exposure causes degradation of electrical characteristics of long term, it is necessary to develop and optimize alternative structures. With the aim of developing and analyzing n type silicon solar cells, it was analyzed and implemented a fabrication process for n+np+ cells with selective emitters formed by laser radiation. To reduce the superposition problems of the laser beam and avoid cycles of melting and solidification of regions in the silicon wafer, parameters of the laser were varied, such as scan speed, frequency of pulses and focus. Solar cells with selective and homogenous emitters were manufactured and characterized. Regarding the scanning electron microscopy, it was observed that with a scan speed of 3000 mm/s and frequencies of pulses of 20 kHz and 30kHz (pattern 1 and 2, respectively), and three levels (A, B and C) of laser focus, circular cavities with diameters of 60 μm to 110 μm were formed. The maximum efficiency in n+np+ with homogenous emitters was 15.2% and, with selective emitters and focused laser beam (pattern A1) was 13.8%. It is important to point out that there were solar cells with selective emitter that were more efficient than with homogenous emitters in four out of the five processes, and in the same processing batch, the most efficient solar cell with homogenous emitter reached 13.1%. Regarding the device illuminated on the p+ face, in this case operating as a p+nn+ cell, the maximum efficiency was obtained with the A2 pattern, being 12.9% efficient, exceeding the highest value previously obtained in NTSolar/ PUCRS, which was 11,6%.